A 3D and Stable Lithium Anode for High‐Performance Lithium–Iodine Batteries. Issue 33 (20th June 2019) - Li, Kang; Hu, Ziyu; Ma, Jizhen; Chen, Song; Mu, Dexu; Zhang, Jintao
Abstract: Lithium metal is considered as the most promising anode material due to its high theoretical specific capacity and the low electrochemical reduction potential. However, severe dendrite problems have to be addressed for fabricating stable and rechargeable batteries (e.g., lithium–iodine batteries). To fabricate a high‐performance lithium–iodine (Li–I2 ) battery, a 3D stable lithium metal anode is prepared by loading of molten lithium on carbon cloth doped with nitrogen and phosphorous. Experimental observations and theoretical calculation reveal that the N, P codoping greatly improves the lithiophilicity of the carbon cloth, which not only enables the uniform loading of molten lithium but also facilitates reversible lithium stripping and plating. Dendrites formation can thus be significantly suppressed at a 3D lithium electrode, leading to stable voltage profiles over 600 h at a current density of 3 mA cm −2 . A fuel cell with such an electrode and a lithium–iodine cathode shows impressive long‐term stability with a capacity retention of around 100% over 4000 cycles and enhanced high‐rate capability. These results demonstrate the promising applications of 3D stable lithium metal anodes in next‐generation rechargeable batteries. Abstract : The enhanced lithiophilicity of nitrogen/phosphorous‐doped carbon cloth facilitates uniform lithium coating on carbon fibers. This enables the construction of a 3D lithium anode with superior cycling stability for enhanced lithium–iodine battery performance.